1993
DOI: 10.1002/em.2850210309
|View full text |Cite
|
Sign up to set email alerts
|

DNA response to bleomycin in mammalian cells with variable degrees of chromatin condensation

Abstract: BLM induces DNA degradation in living cells. We used CHO cells with maximal chromatin compactness (cells synchronized in metaphase), cells with chromatin decondensed by Na butyrate treatments, and control cells with normal chromatin condensation in order to analyse the correlation between chromatin compactness, DNA sensitivity to BLM, efficiency of repair of BLM-induced DNA lesions, and cell viability. We found that the DNA sensitivity to BLM and the efficiency of DNA repair is inversely correlated with the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…DOI 10.1002/em derived cells, confirming that the chromosomes of mammalian cells exhibit differential sensitivity to BLM [Povirk and Austin, 1991]. Although further studies are needed to determine the reason for this difference, a lower level of BLM-induced DNA damage, a greater repair efficiency, and perhaps more efficient BLM hydrolases could be factors explaining why CPC cells are less sensitive than CHE cells to BLM-induced chromosomal damage López-Larraza and Bianchi, 1993;Galm et al, 2005]. ( In spite of the differential chromosomal sensitivity to BLM exhibited by CHE and CPC cells, both cell lines showed induction of ICE.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…DOI 10.1002/em derived cells, confirming that the chromosomes of mammalian cells exhibit differential sensitivity to BLM [Povirk and Austin, 1991]. Although further studies are needed to determine the reason for this difference, a lower level of BLM-induced DNA damage, a greater repair efficiency, and perhaps more efficient BLM hydrolases could be factors explaining why CPC cells are less sensitive than CHE cells to BLM-induced chromosomal damage López-Larraza and Bianchi, 1993;Galm et al, 2005]. ( In spite of the differential chromosomal sensitivity to BLM exhibited by CHE and CPC cells, both cell lines showed induction of ICE.…”
Section: Discussionmentioning
confidence: 91%
“…The fact that chromosomal incompleteness is much more frequent in BLM-treated cells than in ionizing radiation-exposed cells could be due to the complexity of the DNA damage after BLM treatment, since, unlike ionizing radiation, this antibiotic intercalates in the DNA inducing single-and double-strand breaks. The sensitivity of DNA to BLM and the efficiency of the repair of DNA lesions induced by this compound are modulated by several factors, including the base composition [Takeshita et al, 1978], the chromatin structure [Vig and Lewis, 1978;Bianchi et al, 1990;López-Larraza et al, 1990;López-Larraza and Bianchi, 1993], and the activity of BLM-hydrolase [Chen and Stubbe, 2005;Galm et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…One model is that CHD4's presence in the complex indicates that ATR is associated with heterochromatin. Early work on DNA damage focused on how repair could occur in DNA condensed in nucleosomes and some studies indicate that repair enzymes have difficulty accessing condensed DNA ( , ). In this model, ATR could be the guardian of heterochromatin, sampling DNA to check for damage in densely compacted DNA by unfolding and refolding heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…There is abundant information indicating that the chromosomal sensitivity of mammalian cells to clastogenic compounds is closely related with the chromatin fibril structure [Kuo and Hsu, 1979;Kuo, 1981;López-Larraza and Bianchi, 1993;Smith et al, 1986]. Recently, we analyzed the sensitivity to SN of CHO chromosomes substituted with different halogenated compounds and found that DNA substitution with BrdUrd or IdUrd potentiates the chromosome damage induced by the antibiotic.…”
Section: Discussionmentioning
confidence: 99%